Murine erythroleukemia cell line GM979 contains factors that can activate silent chromosomal human gamma-globin genes. - Zitnik, G (1991)
We introduced a normal chromosome 11 into GM979 murine erythroleukemia cells by fusing them with Epstein-Barr virus-transformed lymphocytes from a normal individual. In contrast to previous data obtained with other murine erythroleukemia cells, we detected activation of human chromosomal gamma-globin genes in GM979 cells. GM979, unlike previously used murine erythroleukemia cell lines, expresses murine embryonic globin in addition to adult globin. While all the hybrids expressed gamma- and beta-globin, they displayed a wide range of gamma-globin expression in relation to that of beta-globin. No correlation, however, was found in quantitative expression between murine embryonic globin and human gamma-globin in these hybrids, suggesting that the two globins are regulated independently, at least in this cell line. These data indicate that gamma-globin genes from normal, nonerythroid chromosomes are not irreversibly silenced, and they can be activated by a positive trans factor(s) present in GM979 cells.